Dysfunctional Personality Beliefs Linked to Emotion Recognition Deficits in Individuals With Cocaine Addiction and Personality Disorders - Albein-Urios, Natalia; Martinez-Gonzalez, Jose M.; Lozano-Rojas, Oscar; Verdejo-Garcia, Antonio (Frontiers in Psychiatry, 2019)
Background: Facial emotion recognition is impaired in addiction and personality disorders. Dysfunctional personality beliefs reflect negative interpersonal schemas that may underpin emotion recognition deficits. We aimed to examine the association between personality beliefs and emotion recognition among participants with cocaine use disorder including those with comorbid personality disorders. Methods: We recruited 70 participants with cocaine use disorder aged between 19 and 52 who had used 14 g of cocaine over 4.8 years on average. Thirty-eight participants had an additional personality disorder (11 Borderline, 7 Histrionic, 5 Antisocial, 10 Avoidant, and 5 Obsessive–Compulsive). Dysfunctional beliefs were indicated with the Personality Belief Questionnaire, and facial emotion recognition was indicated with the Ekman’s Test. We applied correlations/multiple regressions to test the relationship between beliefs and emotion recognition. Results: Personality beliefs reflecting paranoid, borderline, and antisocial schemas were negatively associated with emotion recognition. Antisocial beliefs were associated with poorer recognition of fear, and paranoid beliefs with poorer recognition of disgust. Antisocial beliefs were significantly associated with emotion recognition after adjusting for cocaine use. Conclusion: Dysfunctional personality beliefs are associated with poorer emotion recognition in cocaine addiction. Personality-related negative schemas about the self and others can impact social cognition and interaction during cocaine treatment.